Surface Quality of a Groove after Trochoidal Milling with a Monolithic Ceramic Milling Cutter - Slabejova, Silvia; Holubjak, Jozef; Czanova, Tatiana; Timko, Pavol; Horak, Andrej; Prokein, Denis (Manufacturing Technology Journal, 2022)
Hard-to-machine materials conclude a variety of materials. In this group of materials are high-strength, hardness-resistant steels, such as austenitic steels, but also non-ferrous alloys with high cor-rosion, heat resistance and strength based on nickel, titanium or cobalt, etc. For machining of these materials, it is necessary to choose suitable tools. The improper cutting tool can cause an increase in geometric inaccuracies, rapid wear, etc. Cutting material is an important factor during designing of cutting tools. A combination of a proper cutting tool with the trochoidal milling can reduce maching time, extend tool lifetime and reduce production costs.
Keywords: Surface Quality; Trochoidal Milling; Ceramics